2006
DOI: 10.1159/000089782
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials in the Management of Inflammatory Bowel Disease

Abstract: Many experimental and clinical observations suggest a potential role for intestinal microflora in the pathogenesis of inflammatory bowel disease (IBD). Manipulation of the luminal content using antibiotics may therefore represent a potentially effective therapeutic option. However, the available studies do not support the use of antimicrobials in ulcerative colitis and larger studies are required. These drugs are however effective in treating septic complications of Crohn’s disease (CD). The use of antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Rifaximin, an efficient gut-specific antibiotic because of its zwitterionic property, which inhibits absorption into the systemic circulation (Marchi et al, 1985), has been shown to be beneficial in specific cases of IBD (Gionchetti et al, 2006). Using a mouse model that accurately expresses human PXR, the present study clearly demonstrates that rifaximin protects through a PXR-dependent mechanism and not as a general antibiotic in both DSS-and TNBS-induced IBD.…”
Section: Discussionmentioning
confidence: 64%
“…Rifaximin, an efficient gut-specific antibiotic because of its zwitterionic property, which inhibits absorption into the systemic circulation (Marchi et al, 1985), has been shown to be beneficial in specific cases of IBD (Gionchetti et al, 2006). Using a mouse model that accurately expresses human PXR, the present study clearly demonstrates that rifaximin protects through a PXR-dependent mechanism and not as a general antibiotic in both DSS-and TNBS-induced IBD.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, RIFax was beneficial in ulcerative colitis and Crohn's disease (CD), two chronic inflammatory diseases generally referred to as inflammatory bowel diseases (IBDs). Despite the differences in dose and duration, RIFax was beneficial in active ulcerative colitis, mild-to-moderate CD as well as prevention of postoperative recurrence of CD (Shafran and Johnson, 2005;Gionchetti et al, 2006;Guslandi et al, 2006). The mechanism contributing to the beneficial effects of RIFax in chronic gastrointestinal disorders are not fully understood.…”
mentioning
confidence: 99%
“…In UC patients with moderate to severe disease and in patients who failed to respond to 5-ASA compounds, systemic corticosteroids should be used. To minimize side effects, corticosteroids should be gradually reduced as soon as the disease remission is achieved [13][14][15]. Surgery or immunomodulator is considered for patients with corticosteroid-dependent or unresponsive to corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A greater understanding of the pharmacodynamics and kinetics of nicotine in relation to the immune system and enhanced knowledge of gut permeability defects in UC are required to establish the exact protective nature of nicotine and its metabolites in UC. This review suggests possible hypotheses for the protective mechanism of nicotine in UC, highlight the relationship between gut permeability and inflammation, and indicates where in the pathogenesis of the disease nicotine may mediate its effect [1][2][3][12][13][14]. UC is predominantly a disease of non-smokers, and nicotine may be the agent responsible for this association.…”
Section: Nicotinementioning
confidence: 99%